COMBINATION EXERCISE IN LUMBAL SPONDYLOSIS DISEASE - Deasy Virka Sari; Linda Pramusinta (Physiotherapy and Physical Rehabilitation Journal, 2022)
Back pain is a common complaint in everyday life. Low back pain remains a major public health burden throughout the industrialized world. Epidemiological data showing low back pain ranks 19th with a percentage of 27% and a lifetime prevalence of 60%. Various data in several developing countries state that the incidence of low back pain is approximately 15-20% of the population, most of which are acute or chronic low back pain, including the benign type. Functional limitations include difficulty bending, walking for a long time, and sitting for a long time because of the pain. Assessment of signs and symptoms is very important to the planning and evaluation. Benefits for Academics This research is expected to add scientific insight to personnel who want to know about case reports of lumbar spondylosis in the elderly. Interviews were conducted by filling out a questionnaire with the researcher's guide. Exercise Performing exercises with the guidance of the researcher, which includes an operating system for physiotherapy intervention procedures. Case report The researcher conducted a literature review related to the combined exercise of lumbar spondylosis in the elderly.